Handbook of filterable viruses - Fairbrother, R. W. (Ronald Wilson) (William Heinemann Ltd., 1934)
Handbook of Filterable Viruses present a general survey of the filterable viruses, particularly those causing disease in man. This book is composed of eight chapters, and begins with an overview of the history and research works on filterable viruses. The next chapters describe the nature, cultivation, and methods of analysis of these viruses, as well as the epidemiology, immunity, and classification of infectious diseases caused by them. The remaining chapters explore the numerous diseases considered to be caused by filterable viruses. This book will prove useful to biochemists, bacteriologis.